Clickers in EFL Classrooms: Evidence from Two Different Uses - Caki̇roglu, Unal; Erdogdu, Fath; Gokoglu, Seyfullah (Bastas Publications, 2018)
Clickers as electronic response systems allow students to respond instantly to questions. The aim of this study is to compare the effects of using clickers on student participation during different periods of EFL courses. The intervention was implemented in question–response sessions of an EFL course at a secondary school. A quasi-experimental design was used in which twenty participants were assigned to two groups, Group A ( n = 10) and Group B ( n = 10). The implementation process is divided into three periods. In the preparation period, both of the groups did not use clickers, in the first period while the Group A used clickers, Group B continued without using clickers in the lessons. Then in the second period; in contrary, Group A and Group B students changed the roles in using the clickers; that is Group B started with clickers in the second period and Group A followed the lesson without clickers. When the clickers used the students’ participation rates were determined by clicker system records and an observation form is used when non-clickers strategies were used. As a result, even if they used clickers in different time periods both Groups A and B increased their participation rates while using clickers. Moreover, when the students in Group A were non-clickers, their correct answer rates were decreased. In contrast, when the students in Group B were non-clickers, their correct answer rates were increased. Results showed that even after students ceased to use clickers, positive effects on participation continued; however, the quality of the students’ answers declined. Along with the study findings, suggestions for clickers use in various periods of the courses are included.
Keywords: Participation; Clickers; Traditional response strategies; Language teaching; 4. Education; 16. Peace & justice; 3. Good health